Paradox of Corporate Social Responsibility and Sustainability - Singgih Bayu Indra Hermawan; Sari Dewi; Erizal Wibisono Santoso (Universitas Muhammadiyah Metro, 2026)
This research aims to interpret paradox of Corporate Social Responsibility through the annual and sustainability reports of PT Sat Nusapersada Tbk This study uses a strict reading method as data collection technique and reinterpretation as data analysis. The findings of this study are the existence of paradox behind the sustainability report. The paradox is in the form of a meaning that has another meaning. Therefore, this clashes with several indications of the report’s objectives. The theoretical implication is that Psychoanalysis can be used as a technical analysis seen from the seriousness of the company in reporting its annual and sustainability reports. This has an impact in practice, can assist auditors in carrying out their duties through the language written in their reports. The novelty is relationship between accounting and Å½iÅ¾ekian Psychoanalysis in the results of this research, thus forming a new uniqueness.